Agar-based aqueous electrolytes for electrochemical capacitors with reduced self-discharge. (1st February 2020) - Menzel, Jakub; Frąckowiak, Elżbieta; Fic, Krzysztof
Abstract: This paper reports on the electrochemical performance of symmetric carbon/carbon electrochemical capacitors operating in aqueous electrolyte (0.5 mol L −1  K2 SO4 solution) and modified with various amounts of agar (up to 5 wt%). It has been found that a change in electrolyte form (from liquid to gel-like) increases the hydrogen storage efficiency on the negative electrode (confirmed by operando Raman spectroscopy), improves the cycle life at elevated voltages and reduces the self-discharge. Furthermore, it has been found that the gas generation rate during capacitor operation is remarkably diminished (by ca. 4 times), and thus, the detrimental impact of increased internal pressure is noticeably reduced. Graphical abstract: Image 1